Metoxifluran, an inhalation analgesic that opens up new possibilities in anesthesia - Dmytriev, Dmytro; Nazarchuk, Oleksandr; Babina, Yuliana (Pain medicine, 2023)
Although numerous clinical guidelines for pain management have been published over the past decade, inadequate pain relief remains a major public health problem. Currently, several methods of analgesia are available for the treatment of acute pain, including intravenous analgesia, epidural anesthesia, and oral administration of medications. However, the existing methods of analgesia still do not cover all the needs of proper analgesia, the search for new forms of release, methods of administration and methods of analgesia continues. Currently, non-invasive methods of analgesia are being actively implemented, which include a transdermal delivery system of analgesics (in particular, fentanyl hydrochloride), intranasal and inhalational analgesia, in which the delivery of analgesics is controlled by both the doctor and the patient. The purpose of this article is to review the inhaled analgesic methoxyflurane, which is administered by means of an individual inhaler and is used for the treatment of acute pain.